The Relationship between Postural Control and Muscle Quality in Older Adults. Issue 3 (4th May 2022) - Walsh, Gregory S.; Low, Daniel C.; Arkesteijn, Marco
Abstract: This study aimed to determine relationships between muscle quality, the ratio of muscle strength to muscle mass, and postural control and compare postural control of older adults with higher and lower muscle quality. Twenty-five older adults had leg muscle quality and postural control with eyes open and closed measured. Linear and non-linear postural control variables were calculated from center of pressure movements. There was a significant canonical correlation between muscle quality and sway complexity, but no relationship between muscle quality and sway magnitude. Higher muscle quality older adults had greater medio-lateral sway complexity than lower muscle quality older adults. These findings suggest that higher muscle quality relates to greater sway complexity in older adults, suggesting maintenance of muscle quality should be considered important to attenuate postural control declines.